The Influence of Wetted Surface of Super Green B Sponge on Temperature, Relative Humidity of Air and Power Efficiency of Blower at Evaporative Cooling System - Hawa, La Choviya (Jurnal Teknologi Pertanian, 2000)
Temperature and relative humidity of air were factors that influenced the evaporativerate of vegetables. The evaporative rate become higher at high temperature and lowrelative humidity.  This is caused by the high gas partial pressure difference between airof storage and vegetables. One method to slow down the metabolism activity of agricultural product was todecrease air temperature and to increase the relative humidity.  Humidifying the air canbe done by spraying water to the unsaturated air stream.  The sensible heat of air wasused to evaporate the water from liquid phase to gas phase, therefore result thetemperature of process became lower than before.  This process called evaporativecooling which its and the mechanism was heat transfer between air and water. The objectives of this research was utilizing evaporative process and knowing theinfluence of wetted surface on temperature, relative humidity and power blower efficiency. This study was performed using seven treatments at evaporative cooling system i.e. :no sponge,1 sponge layer, 2 sponge layer, 3 sponge layer, 1 sponge + water, 2 sponge +water, 3 sponge + water.  The parameters measured were dry bulb and wet bulbtemperatures process, air pressure of fan, temperature and relative humidity of air room,temperature of water from nozel.  To analize the parameters used thermodynamicanalizes without factorial design. The result showed that the thicker wetted surface applied with spraying water thelower temperature gained and the relative humidity become higher.  The greatest temperature decrease in 3 sponge + water treatment was 2.29°C, relative humidity89.09% and the lowest temperature decrease in 1 sponge+water treatment was 1.74°C and relative humidity was 85.27%.  The addition of sponge with spraying water wouldreduce the mass rate of air output from blower and decrease the power blower efficiency. The highest power efficiency in 1 sponge layer treatment was 62.93% and the lowestpower efficiency in 3 sponge + water treatment was 22.57%.Keyword : evaporative coolin, sponge, and humidifying